Factors Related to the Quality of Life of Patients with Pulmonary Tuberculosis - Dedi Wahyudi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pulmonary tuberculosis remains a serious problem in Indonesia, especially in West Java and Sukabumi, with treatment lasting a minimum of 6 months requiring a high commitment from patients. Factors such as duration of illness, length of treatment, social stigma, and adherence greatly affect the quality of life of patients. This study aims to analyze the factors related to the quality of life of pulmonary tuberculosis patients in the Work Area of UPTD Puskesmas Sukabumi, Sukabumi City. The research design used is correlational with a cross-sectional approach. The population includes all pulmonary tuberculosis patients in the Work Area of UPTD Puskesmas Sukabumi, Sukabumi City, with a sample of 40 respondents selected using a total sampling technique. Data collection was conducted using questionnaires which is declared valid and reliable using the pearson's product moment and cronbach's alpha test. Univariable analysis employed frequency distribution, and bivariable analysis used the chi-square test. The research findings indicate that there is a significant relationship between the duration of illness and the quality of life of tuberculosis patients with a p-value of 0.009, the duration of treatment and quality of life with a p-value of less than 0.001, social stigma and quality of life with a p-value of less than 0.001, as well as treatment adherence and quality of life with a p-value of less than 0.001. There is a relationship between the duration of illness, length of treatment, social stigma, and treatment adherence with the quality of life of pulmonary tuberculosis patients in the Work Area of UPTD Puskesmas Sukabumi, Sukabumi City.